An Exceptional Case of Ileocolic Intussusception Secondary to Burkitt’s Lymphoma: What Variations Are There in the Presentation and Management of Those Patients Who Approach Adolescence? - Krish Kulendran; Kay Tai Choy; Cian Keogh; Dinesh Ratnapala (Case Reports in Surgery)
Intussusception is a common cause of abdominal pain among the paediatric population with up to 10% of cases occurring secondary to a pathological lead point. Burkitt’s lymphoma (BL) is a highly malignant and rapidly growing B-cell neoplasm which in extremely rare cases can present as intussusception. We report a case in an otherwise healthy 15-year-old male who presented with atypical abdominal pain. Imaging subsequently indicated an ileocolic intussusception, and given that the suspicion of a pathological lead point mandates a laparotomy and bowel resection, he proceeded to surgery. The histopathology confirmed Burkitt’s lymphoma as the aetiology responsible for this intussuscepted mass. A detailed discussion including a systematic review of all previous case reports explore the diagnostic dilemma of intussusceptions secondary to BL. This case report aims to highlight the clinical challenges in establishing such a diagnosis and an appreciation for the subtle variations in clinical features, as well as the differences in management between infants and adolescents.